Blood Plasma of Patients with Parkinson's Disease Increases Alpha-Synuclein Aggregation and Neurotoxicity. (14th November 2016) - Wang, Peng; Li, Xin; Li, Xuran; Yang, Weiwei; Yu, Shun
Abstract : A pathological hallmark of Parkinson's disease (PD) is formation of Lewy bodies in neurons of the brain. This has been attributed to the spread of α -synuclein ( α -syn) aggregates, which involves release of α -syn from a neuron and its reuptake by a neighboring neuron. We found that treatment with plasma from PD patients induced more α -syn phosphorylation and oligomerization than plasma from normal subjects (NS). Compared with NS plasma, PD plasma added to primary neuron cultures caused more cell death in the presence of extracellular α -syn. This was supported by the observations that phosphorylated α -syn oligomers entered neurons, rapidly increased accumulated thioflavin S-positive inclusions, and induced a series of metabolic changes that included activation of polo-like kinase 2, inhibition of glucocerebrosidase and protein phosphatase 2A, and reduction of ceramide levels, all of which have been shown to promote α -syn phosphorylation and aggregation. We also analyzed neurotoxicity of α -syn oligomers relative to plasma from different patients. Neurotoxicity was not related to age or gender of the patients. However, neurotoxicity was positively correlated with H&Y staging score. The modification in the plasma may promote spreading of α -syn aggregates via an alternative pathway and accelerate progression of PD.